Frequency-dependent effects of sequenced pulsed magnetic field on experimental diabetic neuropathy. (3rd October 2015) - Mert, Tufan; Gisi, Gokce; Celik, Ahmet; Baran, Furkan; Uremis, Muhammed Mehdi; Gunay, Ismail
Abstract : Purpose : Pulsed magnetic field (PMF) as an important non- invasive alternative therapeutic option has been investigated in several pre-clinical and clinical studies. We also hypothesized that sequenced PMF formed with different frequencies can modulate the diabetes-induced neuropathic signs differently. Materials and methods : Therapeutic actions of sequenced PMF including 1, 5, 1, 5 Hz (low (L)-PMF) or 30, 40, 30, 40 Hz (high (H)-PMF) were examined on improving signs and symptoms of diabetic neuropathic pain in the streptozotocin-induced diabetic rat models by measuring nociceptive parameters such as hyperalgesia and allodynia, and various cytokine levels (tumor necrosis factor [TNF]-alpha, interleukin [IL]-1 beta, IL-6 and IL-10) of spinal cord and sciatic nerve tissues. Results : Ameliorating potential of L-PMF application on signs of diabetes is significantly higher than those of H-PMF. L-PMF partially attenuated the diabetes-induced increase in the blood glucose level, enhanced the decreased thresholds and latency during the experiments. Diabetes enhanced the pro-inflammatory cytokine, TNF-alpha, IL-1 beta and IL-6, levels in spinal cord and sciatic nerve of rats. L-PMF treatments to diabetic rats decreased these, but enhanced the production of anti-inflammatory cytokine, IL-10. Conclusions : The present results demonstrated that sequenced L-PMF treatment can relieve neuropathic signs of diabetes in rats. Anti-hyperglycemic, anti-allodynic and anti-hyperalgesic effects of L-PMF treatment can be closely correlated with each other. Furthermore, decreasing actions of L-PMF on pro-inflammatory/anti-inflammatory cytokine ratio can suggest that the therapeutic potential of L-PMF in diabetes induced neuropathy may involve the regulation of the neuroinflammatory/neuroimmune processes.